Crime, law and society - Feeley, Malcolm (Pioneers in contemporary criminology, 2013)
Coercion and compliance : a new look at an old problem -- The concept of laws in social science : a critique and notes on an expanded view -- A solution to the "voting dilemma" in modern democratic theory -- Legality, social research and the challenge of institutional review boards --The Black basis of constitutional development -- The adversary system -- Two models of the criminal justice system : an organizational perspective -- The process is the punishment -- Bail reform -- Responsive law and the judicial process: implications for the judicial function -- The prison conditions cases and the bureaucratization of American corrections: influences, impacts, and implications -- Implementing court orders in the United States : judges as executives -- The new penology : notes on the emerging strategy of corrections and its implications -- Actuarial justice : the emerging new criminal law -- Crime, social order, and the rise of neo- conservative politics -- Perspectives on plea bargaining -- Legal complexity and the transformation of the criminal process: the origins of plea bargaining -- The vanishing female : the decline of women in the criminal process -- Entrepreneurs of punishment: the legacy of privatization